A Literary Review on Nidana of Amlapittaw.s.r. to Aetiological Factors of Dyspepsia and Various Modern Terms Related to Amlapitta. - Vyas, Dharmendra Kumar Vyas; Saini, Shri Ram; Sevatkar, BK (International Research Journal of Ayurveda & Yoga, 2024)
Dyspepsia is a condition of impaired digestion. Hyperacidity or acid dyspepsia is a very common dietary disorder.Curbing the problem of hyperacidity needs a total overhaul of the dietary regimen in addition to healthy exercise and lifestyle conquering hyperacidity is certainly a very important issue.Prevalence of dyspepsia is about 20-30% worldwide. A study reported that prevalence of dyspepsia to be 30.4% in India.This article discusses the various aetiological factorsof hyperacidity or Dyspepsia(Amlapitta) both Morden and ancient classical texts and various modern many conditions in Modern Science like Gastritis, Gastro-esophageal Reflux Diseases, Dyspepsia, Ulcers can be included under the broad umbrella of Amlapitta.Certain foods (Pitta provocative potency of diet) and lifestyle are considered to promote gastro-esophageal reflux. Foods that have been implicated include coffee, alcohol, chocolate, fatty foods, acidic foods, and spicy foods. Stopping smoking and not drinking alcohol do not appear to result in significant improvement in symptoms. ManasikaHetu[Psychological factors] plays an important role in promoting Amlapitta. elative term with Amlapitta.In this articlevarious symptoms and aetiological factor show that